Pathogen-Mediated Assembly of Plant-Beneficial Bacteria to Alleviate Fusarium Wilt in Pseudostellaria heterophylla - Yuan, Qing-Song; Wang, Lu; Wang, Hui; Wang, Xiaoai; Jiang, Weike; Ou, Xiaohong; Xiao, Chenghong; Gao, Yanping; Xu, Jiao; Yang, Ye; Cui, Xiuming; Guo, Lanping; et al. (Frontiers in Microbiology, 2022)
Fusarium wilt (FW) is a primary replant disease that affects Pseudostellaria heterophylla (Taizishen) and is caused by Fusarium oxysporum, which occurs widely in China under the continuous monocropping regime. However, the ternary interactions among the soil microbiota, P. heterophylla, and F. oxysporum remain unknown. We investigated the potential interaction relationship by which the pathogen-mediated P. heterophylla regulates the soil and the tuberous root microbiota via high-throughput sequencing. Plant–pathogen interaction assays were conducted to measure the arrival of F. oxysporum and Pseudomonas poae at the tuberous root via qPCR and subsequent seedling disease incidence. A growth assay was used to determine the effect of the tuberous root crude exudate inoculated with the pathogen on P. poae. We observed that pathogen-mediated P. heterophylla altered the diversity and the composition of the microbial communities in its rhizosphere soil and tuberous root. Beneficial microbe P. poae and pathogen F. oxysporum were significantly enriched in rhizosphere soil and within the tuberous root in the FW group with high severity. Correlation analysis showed that, accompanied with FW incidence, P. poae co-occurred with F. oxysporum. The aqueous extract of P. heterophylla tuberous root infected by F. oxysporum substantially promoted the growth of P. poae isolates (H1-3-A7, H2-3-B7, H4-3-C1, and N3-3-C4). These results indicated that the extracts from the tuberous root of P. heterophylla inoculated with F. oxysporum might attract P. poae and promote its growth. Furthermore, the colonization assay found that the gene copies of sucD in the P. poae and F. oxysporum treatment (up to 6.57 × 1010) group was significantly higher than those in the P. poae treatment group (3.29 × 1010), and a pathogen-induced attraction assay found that the relative copies of sucD of P. poae in the F. oxysporum treatment were significantly higher than in the H2O treatment. These results showed that F. oxysporum promoted the colonization of P. poae on the tuberous root via F. oxysporum mediation. In addition, the colonization assay found that the disease severity index in the P. poae and F. oxysporum treatment group was significantly lower than that in the F. oxysporum treatment group, and a pathogen-induced attraction assay found that the disease severity index in the F. oxysporum treatment group was significantly higher than that in the H2O treatment group. Together, these results suggest that pathogen-mediated P. heterophylla promoted and assembled plant-beneficial microbes against plant disease. Therefore, deciphering the beneficial associations between pathogen-mediated P. heterophylla and microbes can provide novel insights into the implementation and design of disease management strategies.